2023
DOI: 10.1021/acs.jpcc.3c01253
|View full text |Cite
|
Sign up to set email alerts
|

Aggregates of Cyanine Dyes: When Molecular Vibrations and Electrostatic Screening Make the Difference

Abstract: Aggregates of cyanine dyes are currently investigated as promising materials for advanced electronic and photonic applications. The spectral properties of aggregates of cyanine dyes can be tuned by altering the supramolecular packing, which is affected by the length of the dye, the presence of alkyl chains, or the nature of the counterions. In this work, we present a joint experimental and theoretical study of a family of cyanine dyes forming aggregates of different types according to the length of the polymet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…This indicates quenching of the 670 nm signal, and it is possible if DiI molecules form aggregates in a suitable solvent or medium. Delledonne et al and others reported that DiI has an emission peak at about 575 nm for a range of solvents, and the emission peak is red-shifted in a mixed polar solvent of ethanol and water. They explained this with J-aggregation of the lipophilic dye in polar solvents. Our spectral data also indicate the formation of such DiI aggregates.…”
Section: Resultsmentioning
confidence: 98%
“…This indicates quenching of the 670 nm signal, and it is possible if DiI molecules form aggregates in a suitable solvent or medium. Delledonne et al and others reported that DiI has an emission peak at about 575 nm for a range of solvents, and the emission peak is red-shifted in a mixed polar solvent of ethanol and water. They explained this with J-aggregation of the lipophilic dye in polar solvents. Our spectral data also indicate the formation of such DiI aggregates.…”
Section: Resultsmentioning
confidence: 98%
“…[20] Here, our attention is focused on how the solvent polarity and capability to donate or accept hydrogen bonds influences the aggregation status and, consequently, ODIN's spectroscopic properties. Absorption and emission spectra are expected to be very sensitive probes of intermolecular interactions, [26,27] but to fulfill a complete understanding of the aggregation status and its consequences on photo-physics, ultrafast transient absorption spectroscopy, transient infrared spectroscopy and quantum chemical calculations (density functional level of theory, DFT) have been used. DMSO and CHCl 3 have been chosen as solvents, respectively representing a polar and highly prone to accept hydrogen bonds environment and a scarcely polar and poorly capable of forming hydrogen bonds environment.…”
Section: Absorption Emission and Fluorescence Relaxation Propertiesmentioning
confidence: 99%